2008
DOI: 10.1007/s10096-008-0670-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative T-cell interferon-gamma responses to Mycobacterium tuberculosis-specific antigens in active and latent tuberculosis

Abstract: The objective was to compare the quantitative T-cell responses measured by the commercial interferon-gamma (IFNgamma) release assays (IGRAs) in active and latent tuberculosis (TB) states. T-cell responses of culture-proven TB cases were compared with those of contacts with positive IGRA results and tuberculin skin tests >or= 15 mm. T-SPOT.TB results in 270 active TB cases and 183 community contacts showed the median spot-forming cells (SFCs) above negative control/2.5 x 10(5) peripheral blood mononuclear cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 11 publications
5
36
1
Order By: Relevance
“…The increased production of mycobacterium-specific IFN-␥ found in BAL, lymph node, and PBMC among activedisease monkeys likely reflects the increased bacterial burden among this group. Similarly, the greater production of IFN-␥ from PBMCs in humans with active disease compared to that of latently infected individuals has been documented (4,10,11,13,14,19,26). In each of the studies, a wide range of results is demonstrated within each clinical group (active versus latent), reflecting a wide spectrum of disease associated with each clinical classification that also is seen in our model.…”
Section: Vol 77 2009 Nonhuman Primate Model Of Tuberculosis 4639supporting
confidence: 58%
“…The increased production of mycobacterium-specific IFN-␥ found in BAL, lymph node, and PBMC among activedisease monkeys likely reflects the increased bacterial burden among this group. Similarly, the greater production of IFN-␥ from PBMCs in humans with active disease compared to that of latently infected individuals has been documented (4,10,11,13,14,19,26). In each of the studies, a wide range of results is demonstrated within each clinical group (active versus latent), reflecting a wide spectrum of disease associated with each clinical classification that also is seen in our model.…”
Section: Vol 77 2009 Nonhuman Primate Model Of Tuberculosis 4639supporting
confidence: 58%
“…However, a lack of evidence for latent status is a limitation of the present study. Further immunological tests, including interferon gamma release assay (IGRA) tests [23][24][25][26][27] and follow-up should be conducted, although the role of interferon-gamma in high-burden areas remains controversial [28]. In the present survey, 14.5% of the patients did not have available chest film images, and 8 of them had TB after gastric cancer treatment.…”
Section: Discussionmentioning
confidence: 87%
“…Studies with experimentally infected animals support this possibility (5). Indeed, many studies conducted with IGRAs have shown higher IFN-␥ responses in active TB patients than in LTBI cases (17,73,74,164). Discordant results, however, have also been obtained (113).…”
Section: Cellular Immune Responses and Infection Statementioning
confidence: 94%
“…Discordant results, however, have also been obtained (113). The disease-associated increase seems to be more evident with the enzyme-linked immunospot (ELISPOT) assay, an assay enumerating IFN-␥-producing cells, than with enzyme-linked immunosorbent assay (ELISA), which measures the levels of IFN-␥ secreted by the cultured cells (17,18,39,40,79,80,118). Thus, the two assays may have different sensitivities.…”
Section: Cellular Immune Responses and Infection Statementioning
confidence: 99%